1981
DOI: 10.1161/01.res.49.6.1268
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial composition and function in diabetes. The effects of chronic insulin use.

Abstract: SUMMARY This study was undertaken in an animal model of mild diabetes to determine if provision of chronic insulin replacement during postprandial hyperglycemia may modify the abnormalities of myocardium. Group 1 served as controls with normal glucose tolerance by intravenous testing. Two additional groups were made diabetic -with low doses of alloxan. Diabetic animals of Group 2 were untreated (re = 8). Group 3 animals (re = 6) received regular insulin daily to reduce postprandial hyperglycemia. After one yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(64 citation statements)
references
References 33 publications
3
58
0
3
Order By: Relevance
“…Similar changes have been reported for the hearts from streptozotocin-diabetic rats which had substantially more myocardial connective tissue [28] and statistically significant increases in the width of myocardial capillary basal lamina [29]. Although in dogs with a mild alloxan diabetes, hydroxyproline values indicated increased amounts of collagen in the myocardium [30], similar measurements in streptozotocin-diabetic rat ventricles showed levels which were significantly increased only at 6 weeks of diabetes [31]; since in the present study only type VI collagen was found to be increased, the unchanged hydroxyproline values of the other collagens would mask this change.…”
Section: Discussionsupporting
confidence: 80%
“…Similar changes have been reported for the hearts from streptozotocin-diabetic rats which had substantially more myocardial connective tissue [28] and statistically significant increases in the width of myocardial capillary basal lamina [29]. Although in dogs with a mild alloxan diabetes, hydroxyproline values indicated increased amounts of collagen in the myocardium [30], similar measurements in streptozotocin-diabetic rat ventricles showed levels which were significantly increased only at 6 weeks of diabetes [31]; since in the present study only type VI collagen was found to be increased, the unchanged hydroxyproline values of the other collagens would mask this change.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the chronic defect of circulating insulin must depress the enzyme activity of cardiac sarcolemma. Indeed, an increased intracellular Na + concentration was also observed in diabetic heart muscle [28]. As shown earlier, the Na+/K+-ATPase activity was reduced in the diabetic heart [29].…”
Section: Discussionsupporting
confidence: 62%
“…Glucose intolerance in a normotensive canine model has been associated with diastolic dysfunction and interstitial fibrosis of the ventricle. 34 In humans, diastolic dysfunction found in hypertensive patients is enhanced by moderate obesity and abnormal glucose metabolism. 35,36 Glucose in itself may be implicated in this increased collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%